A designed room-temperature triplet ligand from pyridine-2, 6-diyl bis(tert-butyl nitroxide). Issue 4 (30th November 2015) - Kawakami, Hinako; Tonegawa, Asato; Ishida, Takayuki
Abstract : The ligating ability ofMesPyBN to formY-MesPyBN was proven, and the low-lying triplet state was maintained after complex formation. Abstract : The magnetic study on newly developed 4-mesitylpyridine-2, 6-diyl bis( tert -butyl nitroxide) shows that almost the whole population has a ground triplet state at room temperature, and the ability of complex formation as a tridentate triplet ligand was proven with a diamagnetic yttrium(iii ) ion.